Determinants of Scabies Symptoms in Students at Al Falah Sukajaya Islamic Boarding School in 2024 - Fadillah Fadillah Nurtafiana; M. Ridwan; Puspita Sari; Fajrina Hidayati; Rifqi Azhari (Lembaga Pengembangan Kinerja Dosen, 2024)
Introduction: The prevalence of scabies cases in Palembang from data from the Ministry of Health of the Republic of Indonesia in January 2020 was 8.3% and December 2020 was 4.5%. The incidence of scabies in Islamic boarding schools is still very high. There are 20 dormitories that can accommodate 10 to 15 students, with foam mattresses lined up for sleeping and stacked when not in use. There are also 4 bathrooms and toilets with large toilets. The source of water used daily is well water which may be brown in color. The habit of changing towels, prayer equipment, clothes, hand towels, even soap. Research Method: The type of research to be carried out is Quantitative research with a Cross Sectional design and a sampling method, namely simple random sampling. The location of the research is at the Al-Falah Sukajaya Islamic Boarding School, Bayung Lencir District, South Sumatra Province. The analysis used in this study is the Chi Square Test. Research Results: The sample in this study amounted to 77 people. The symptoms of scabies with the highest frequency of experiencing symptoms of scabies were 48 (62.4%) respondents, while those who did not have symptoms were 29 (37.7%) respondents. The results of this study indicate that knowledge has a p-value of 0.000 (p = <0.05), the knowledge of students has a p-value of 0.000 (p = <0.05), the role of Islamic boarding school officers has a p -value of 0.0030 (p = <0.05), and the utilization of facilities and infrastructure p-value 0.004 (p = <0.05) with the incidence of scabie Conclusion: Lack of knowledge of students, student behavior, the role of Islamic boarding school elders, utilization of health facilities and infrastructure can increase the risk of scabies. Therefore, it is hoped that there will be improvements in the health aspects of students, such as education and supervision of students, training for officers, and optimal utilization of facilities and infrastructure.